Enhanced DQE and sub-pixel resolution by single-event processing in counting hybrid pixel electron detectors: A simulation study - Zambon, P. (Frontiers in Physics, 2023)
Detective quantum efficiency (DQE) is a prominent figure of merit for imaging detectors, and its optimization is of fundamental importance for the efficient use of the experimental apparatus. In this work, I study the potential improvement offered by data processing on a single-event basis in a counting hybrid pixel electron detector (HPD). In particular, I introduce a simple and robust method of single-event processing based on the substitution of the original cluster of pixels with an isotropic Gaussian function. Key features are a better filtering of the noise power spectrum (NPS) and readily allowing for sub-pixel resolution. The performance of the proposed method is compared to other standard techniques such as centroiding and event normalization, in the simulated realistic scenario of 100 keV electrons impinging on a 450 μm-thick silicon sensor with a pixel size of 75 μm, yielding the best results. The DQE can potentially be enhanced over the entire spatial frequency range, increasing from 0.86 to nearly 1 at zero frequency and extending up to 1.40 times the physical Nyquist frequency of the system thanks to the sub-pixel resolution capability.